Rush desensitization with a single antigen induces subclinical activation of mast cells and protects against bystander challenge in dually sensitized mice. Issue 4 (16th January 2019) - Killoran, Kristin E.; Kropp, Laura E.; Lindrose, Alyssa R.; Curtis, Holly E.; Cook, David; Mitre, Edward
Summary: Background: Rush desensitization can provide short‐term tolerance to individuals who are allergic to certain medications in instances where other therapeutic interventions are limited. While rush desensitization (DS) is typically successful in preventing adverse type I hypersensitivity reactions, the mechanism of allergic protection remains unknown. Given the rise in prevalence of individuals displaying multiple allergies, understanding the impact of rush DS on "bystander" allergens, or additional allergens to which an individual is sensitized, could help inform clinical recommendations. Objective: To evaluate the effect of rush DS on bystander sensitization. Materials and Methods: We used a murine model of rush DS, whereby BALB/c mice were sensitized to ovalbumin (OVA) and desensitized through repeated intraperitoneal injections of OVA. Using a local anaphylaxis assay, we measured ear swelling by Evans blue extravasation following intradermal challenge. In studies to measure the impact on bystander antigens, a modified protocol was used in which mice were dually sensitized to OVA and Keyhole limpet hemocyanin (KLH), and densensitized to either OVA or KLH prior to allergic challenge. Results: The immunological effects of rush DS were independent of changes in Th1 and Th2 cytokine production and circulating OVA‐IgE levels. Instead, rush DS resulted in subclinical degranulation of mast cells prior to challenge. In our dual sensitization model, rush DS with a single antigen conferred protection against allergic challenge to a secondary antigen. Bystander protection required prior sensitization, as DS with an irrelevant antigen did not impact allergic responsiveness. Conclusions and Clinical Relevance: We reveal that a key mechanism of rush DS protection against allergic responsiveness may be the subclinical degranulation of mast cells. Therefore, performing rush DS to a single antigen to which one is IgE‐sensitized may be sufficient to desensitize to multiple allergens. Future studies could lead to streamlined protocols of rush DS for patients with multiple allergies.